Effects of Oligomeric Procyanidins From Lotus Seedpod on the Retrogradation Properties of Rice Starch - Feng, Nianjie; She, Shaowen; Hu, Hengfeng; Tang, Shimiao; Tan, Jiangying; Wu, Qian; Xiao, Juan (Frontiers in Nutrition, 2021)
The extent of retrogradation strongly affects certain physical and cooking properties of rice starch (RS), which are important to consumers. In this study, oligomeric procyanidins from lotus seedpod (LSOPC) was prepared and used to investigate its inhibitory effect on RS retrogradation. Various structural changes of RS during retrogradation were characterized by differential scanning calorimetry, low field nuclear magnetic resonance, X-ray diffraction, scanning electron microscopy, and Fourier transform infrared spectroscopy. The results showed LSOPC could effectively retard both short- and long-term retrogradation of RS, and its inhibitory effect was dependent on the administered concentration of LSOPC. Molecule simulation revealed the interactions of RS and LSOPC, which indicated that the competition of hydrogen bonds between RS and LSOPC was the critical factor for anti-retrogradation. This inhibitory effect and mechanism of action of LSOPC could promote its applications in the field of starch anti-retrogradation.